Consumption convergence across countries: measurement, antecedents, and consequences - Ozturk, Ayse; Cavusgil, S. Tamer; Ozturk, O. Cem (Journal of International Business Studies, 2021)
Are consumers across countries becoming more similar over time in terms of their spending across product categories? If so, what are the antecedents and consequences of convergence in consumption? These questions are of interest to scholars and managers alike. To examine them, we propose a novel empirical framework that encompasses: (1) a new measure of consumption convergence (budget allocation gap), and (2) an econometric model that links consumption convergence to its antecedents and consequences of convergence. Our empirical analyses – using data from 71 countries in 21 product categories between 1990 and 2017 – suggest that, overall, consumption patterns have been converging across countries. Yet, the speed of consumption convergence has been decelerating over time. We also show that consumption convergence is influenced by several previously unexplored antecedents, including technological advances, inward trade openness, and ethnic diversity. Of direct interest to managers and policymakers is the finding that the higher the level of consumption convergence, the higher the market concentration. These findings offer key implications for scholars, managers, and policymakers regarding global marketing strategy and audit, global demand forecasting, international market segmentation and penetration, and global competition.